Pilarização das argilas Montmorilonita e Estevensita com oligômero de alumínio. Caracterização e estudo de propriedades catalíticas em reações de hidroisomerização de n-octano - Oliveira, Ana Lúcia Nunes Falcão de (2004)
Two clays of the smectites type, a montmorillonite from the region of Campina Grande (Pb) and the stevensite of Marrocos were used in the process of intercalation and pillarization. Through the results of spectrophotometry of atomic absorption ICP-AES the chemical composition of the montmorillonite was determined as(Na0,43K0,22Ca0,09)(Al1,48,Mg0,18,Fe0,34)2Si4O10(OH)2. By the same process, the composition of the stevensite was determined as (Li0.09Na0.04K0.03Ca0,05)(Al,Mg,Fe)2(Si,Fe,Al)4O10(OH)2. The values of the specific areas were 29 m2.g-1 and 228 m2.g-1, before the intercalation and 106 m2.g-1 and 219 m2.g-1, after the pillarization, for the montmorillonite and stevensite, respectively. The clays were submitted to a treatment for removal of the organic matter and then transformed in the homoionic type with NaCl, and inserted with aluminium complex and pillarization at 500 oC. Through thermogravimetric analysis and X-Ray diffractometry, it was evaluated the influence of the organic matter in the intercalation of the clays. The results showed that the more stable samples were those submitted to treatment with hypochlorate. The stevensite presented catalytic activity of about 15% above the capacity of the montmorillonite, whose maximum was 50% at 315 oC. Its percentage of isomerization however, in the order of 82%, was about 13% more than for stevensite. The production of isomers of the Mono and Di type were similar for the two clays, being of 84% and 16% respectively. The predominant isomers for both clays were 3-methylheptane and 2-4-dimethylhexane. Despite the catalytic activities of the pillared clays having not reached the same levels for zeolites as ZSM-22, the isomerization relative percentages exceeded the figures reported for this zeolite, at the temperature where the activities of these clays are maximum.